Comparison of treatment outcome between first‐line combination immunotherapy (anti‐PD‐L1 or anti‐PD1) with or without chemotherapy and chemotherapy alone in advanced non‐small cell lung cancer patients in tertiary care hospital - Danainut Naratornsirakul; Busyamas Chewaskulyong; Sarawut Kongkarnka; Songporn Oranratnachai (Cancer Medicine)
Abstract Background Despite promising outcomes of first‐line immunotherapy with or without chemotherapy in advanced non‐small cell lung cancer (NSCLC), limited accessibility due to reimbursement was remain the problem in low to middle income countries. This study aimed to evaluate real‐world effectiveness of immunotherapy in patients with advanced NSCLC in Northern Thailand. Method A retrospective, single‐centered cohort, was conducted. Patients with advanced NSCLC who underwent PD‐L1 testing (excluding EGFR and ALK mutations) and were treated with immunotherapy or without chemotherapy or chemotherapy alone were included. The primary end point was progression‐free survival (PFS). The secondary endpoints were overall survival (OS), objective response rate (ORR), and adverse events. Results A total of 123 patients, of which 21 patients received immunotherapy‐based regimen and 102 patients received chemotherapy alone. The median PFS was 11.9 months in immunotherapy‐based group compared to 5.93 months in the chemotherapy group, with a. hazard ratio (HR) of 0.4 (95% confidence interval [CI], 0.23 to 0.68; p = 0.001). Similarly, the median OS was 26.68 months in the immunotherapy‐based group and 11.21 months in the chemotherapy group, with HR of 0.42 (95% CI 0.22–0.8; p = 0.009). ORRs were significantly higher in the immunotherapy‐based group, with 65% of patients showing a response compared to 32% in the chemotherapy group (p = 0.006). Conclusion The result of this real‐world study in patients with advanced stage NSCLC indicate that first‐line immunotherapy‐based regimen was associated with significantly greater PFS, OS, and ORR with a safety profile consistent with pivotal studies.